From Isolation to Engagement: Understanding and Addressing Online Learning Challenges among University Students in Indonesia - Muhamad Uyun; Fitriani Fitriani (AL-ISHLAH: Jurnal Pendidikan, 2025)
The shift to online learning has posed significant challenges for university students, particularly in developing countries. This study explores the obstacles encountered by undergraduate students in the Islamic Psychology program at Raden Fatah State University during their engagement with online education. A qualitative approach was employed, involving semi-structured interviews with 15 undergraduate students. Participants were selected through purposive sampling to ensure diverse perspectives. Data were analyzed thematically to identify recurring patterns and concerns. The analysis revealed four major challenges: technical difficulties, unsupportive learning environments, limited interaction, and low motivation. Students frequently experienced unstable internet connections and inadequate access to necessary learning tools, which hindered their academic engagement. Many also reported a lack of emotional support and physical space conducive to studying. Additionally, minimal interaction with peers and instructors contributed to a sense of isolation, further diminishing students' motivation. To address these issues, the study recommends strategies such as promoting flexible learning schedules, strengthening peer networks, prioritizing emotional well-being, and designing more interactive and engaging content. Institutions are urged to adopt adaptive teaching methods and invest in professional development for educators to improve online learning outcomes. Future studies using mixed-method approaches are suggested to gain a more nuanced understanding of student experiences in digital learning environments.